1989
DOI: 10.1351/pac198961081395
|View full text |Cite
|
Sign up to set email alerts
|

Vapour pressures up to their critical temperatures of normal alkanes and 1-alkanols

Abstract: Values for the critical temperatures and critical pressures, and coefficients of equations for the vapour pressures of normal alkanes and 1-alkanols are given. They are based on surveys of the available data and estimates of the critical properties of the higher members. The resultant vapour-pressure curves show a progressive change in shape and there are corresponding changes in the coefficients of the equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
208
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 252 publications
(218 citation statements)
references
References 2 publications
10
208
0
Order By: Relevance
“…1). Recently Bazaev et al [7] used isothermal (P − ρ) and isochoric (P − T ) break point techniques to extract vapor-pressure data from precise PVT measurements in the temperature range from 423.15 to 503.15 K. These data agree with values calculated from correlations [22,23,27,30,34] and reported experimental data [25,31,[36][37][38][39][40] to within 0.2-0.4%. Lydersen and Tsochev [37] have reported vapor pressures for pure methanol in the temperature range from 494.8 to 511.75 K. These data are about 0.1% higher than the data reported by Zubarev and Bagdonas [31] and by de Loos et al [39], while the data obtained by Kay and Donham [41] and Ambrose et al [40] are higher by 0.3% and 0.2%, respectively.…”
Section: Vapor Pressuressupporting
confidence: 61%
See 4 more Smart Citations
“…1). Recently Bazaev et al [7] used isothermal (P − ρ) and isochoric (P − T ) break point techniques to extract vapor-pressure data from precise PVT measurements in the temperature range from 423.15 to 503.15 K. These data agree with values calculated from correlations [22,23,27,30,34] and reported experimental data [25,31,[36][37][38][39][40] to within 0.2-0.4%. Lydersen and Tsochev [37] have reported vapor pressures for pure methanol in the temperature range from 494.8 to 511.75 K. These data are about 0.1% higher than the data reported by Zubarev and Bagdonas [31] and by de Loos et al [39], while the data obtained by Kay and Donham [41] and Ambrose et al [40] are higher by 0.3% and 0.2%, respectively.…”
Section: Vapor Pressuressupporting
confidence: 61%
“…1. Comparisons of vapor pressures calculated from the equation developed by Ambrose and Walton [34] with values calculated from the correlations reported by other authors are shown in Fig. 2.…”
Section: Vapor Pressuresmentioning
confidence: 77%
See 3 more Smart Citations